Bubble Economics and Structural Change: The Cases of Spain and France Compared - Pablo Agnese; Jana Hromcová (Institute for the Study of Labor (IZA), 2015)
This paper delves into the recent events that led to the formation of the housing bubble in Spain and the resulting structural change that is arguably needed to put the economy back into the right track. For this purpose we calibrate a model with different equilibria descriptive of the labor markets in Spain and France, where the unemployment rates went from the same initial spot to very different levels. In addition to this, we run two counterfactual analyses that throw some more light on the performance of the Spanish labor market and the Spanish housing bubble. Our results suggest that the unemployment rate in Spain has jumped to much higher levels while switching between equilibria or, what is the same, because of structural change. Moreover, our counterfactuals indicate that, first, the Spanish flexibilization reform has fallen short of its own goals and, second, there has been an important misdirection of resources into the construction industry mainly fueled by excessively low real interest rates.
Keywords: J64; O57; 330; structural change; bubble; unemployment; interest rate; productivity